2017
DOI: 10.1038/s41598-017-11504-6
|View full text |Cite
|
Sign up to set email alerts
|

Melt fluxing to elevate the forming ability of Al-based bulk metallic glasses

Abstract: Salt-fluxing treatment is an effective technique to improve the glass-forming ability (GFA) of bulk metallic glass (BMG)-forming melts, as demonstrated before in Pd- and Fe-based systems. However, it has been challenging to develop similar fluxing protocol for more reactive melts, such as Al-rich BMG-forming systems. Here we design new fluxing agents, from a thermodynamics perspective that takes into account combined effects of physical absorption and chemical absorption (reaction) between the fluxing agents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 63 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…25 La 1.75 with a fully glassy rod of 1.5 mm in diameter. Although the glassy rod can reach 2.5 mm for the same composition after a refined fluxtreatment of the liquid [31], this critical size is still much smaller than those of typical Zr-based MGs (~75 mm) [32], Mg-MGs (25 mm) [18] and Pd-MGs (80 mm) [33]. Moreover, the glass forming ability of Al-MGs is very sensitive to compositions.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…25 La 1.75 with a fully glassy rod of 1.5 mm in diameter. Although the glassy rod can reach 2.5 mm for the same composition after a refined fluxtreatment of the liquid [31], this critical size is still much smaller than those of typical Zr-based MGs (~75 mm) [32], Mg-MGs (25 mm) [18] and Pd-MGs (80 mm) [33]. Moreover, the glass forming ability of Al-MGs is very sensitive to compositions.…”
mentioning
confidence: 93%
“…However, one remarkable exception is the family of Al-based MGs [23,24]. Although there have been continuous efforts in optimizing compositions and improving processing techniques since its first discovery [29] several decades ago, the glass forming ability of Al-MGs is still limited nowadays [23,30,31]. Recently, Wu et al [30] reported that the hitherto best glass forming ability for Al-MGs is from Al 86 Ni 6.75 Co 2.25 Y 3.…”
mentioning
confidence: 99%
“…The hot working of amorphous powder needs better thermal stability and higher glass-forming ability (GFA), which needs to produce an excellent amorphous powder. Researchers have been a focused effort that aims to understand the effect of minor alloying additions on GFA and thermal stability and have proposed many theories on structure, thermodynamic and kinetic factors, so as to find out the rule of amorphous formation, optimize the composition design of amorphous alloy and find the amorphous alloy system which are beneficial to later application [5][6][7][8][9][10][11][12][13][14]. It is generally believed that the amorphous alloy system should contain three or more elements, the atomic size difference of the main components should generally be greater than 12% and with a large negative mixing enthalpy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, light-metal-based BMGs have attracted tremendous attention and research. In the past decades, many lightweight BMGs such as Al- [6,7], Mg- [8,9], and Ti-based BMGs [10][11][12][13][14] have been successfully developed. However, the main bottleneck of Al-based BMGs is the relatively low glass-forming ability (GFA) (the maximum critical diameter of only 1.5 mm [6]), while Mg-based BMGs always lack room temperature plasticity even upon compression [8,9].…”
Section: Introductionmentioning
confidence: 99%